Design, synthesis, and insecticidal activity evaluation of novel 4‐(N, N‐diarylmethylamines)furan‐2(5H)‐one derivatives as potential acetylcholine receptor insecticides. Issue 2 (19th September 2018) - Tian, Pingyi; Liu, Dengyue; Liu, Zhengjun; Shi, Jing; He, Wenjing; Qi, Puying; Chen, Jixiang; Song, Baoan
Abstract: BACKGROUND: Flupyradifurone is a member of a novel class of insecticides that possess excellent insecticidal activities. Halogen‐containing phenyl groups are important and indispensable structural components of many pesticides. However, replacement of the difluoromethyl group of flupyradifurone with halogen‐containing phenyl groups has not been reported. Hence, a series of novel butenolide derivatives containing phenyl groups were synthesized and bioassayed to discover novel compounds with excellent insecticidal activities. RESULTS: Some target molecules exhibited good insecticidal activities against Aphis craccivora . Among the title compounds, 4cc showed the best insecticidal activities with an 50% lethal concentration (LC50 ) value of 1.72 μg mL −1, which is superior to that of pymetrozine (LC50  = 6.86 μg mL −1 ). Molecular docking indicated that4cc lacks oxidative metabolism by CYP6CM1 and metabolic resistance with imidacloprid. Furthermore, label‐free quantitative proteomic analysis indicated that4cc may be a potential acetylcholine receptor insecticide that acts on the nicotinic acetylcholine receptor. Compound4cc also decreased the capability for oxidative metabolism, which further supported the molecular docking results. CONCLUSION: This work can be used to further investigate the mechanism underlying the insecticidal activity of butenolide derivatives and develop potential novel butenolide insecticides. © 2018 Society of Chemical Industry Abstract : A series of novel 4‐( N, N ‐diarylmethylamines)furan‐2(5 H )‐one derivatives were designed and synthesized, and the insecticidal activity evaluated. The insecticidal mechanism and oxidative metabolism of highly bioactive compound4cc were investigated.